Semantic Changes and Adaptation of Chinese Characters Related to Worshipping with Radical of 示 (Shì) and 礻 (Shì) - Phiromlertamorn, Phoommarin (Ganesha Journal, 2022)
The purpose of this research is to study the literal meaning, quantity, and adaptation of Chinese characters with the radical of "示" (shì) and "礻" (shì) related to worshipping. By comparing the objects, “Shuo wen jie zi” （说文解字）, “The Contemporary Chinese Dictionary (7th ed.)” （现代汉语词典） and the “Table of General Standard Chinese Characters” (通用规范汉字表), this research will show how Chinese worshipped the change of characters as society progressed and changed in both meaning and quantity. In order to adapt to modern society, the meaning of Chinese worshipped characters have become even more important. Both of the characters with meanings are no longer used in the modern society, and those characters who haven't matched the development and direction of Chinese worship have been eliminated. Such as the complex composition Chinese worship characters. In addition, lately some new Chinese worship characters have appeared in order to adapt to modern society. Such as simplify character pattern and structure, so that there are enough Chinese worship characters to record these.